Vitamin D status in Pulmonary Tuberculosis : a case control study (Bangabandhu Sheikh Mujib Medical University Journal, 2022)
Pulmonary tuberculosis is the major cause of morbidity and mortality in the developing world. In South Asia, 80% of the apparently healthy population have vitamin D deficiency (30ng/ml as normal. Thirty partici- pants in each group were enrolled, from whom serum vitamin D concentration was measured, analyzed and interpreted. Mean serum vitamin D level was significantly low in case group than control group (p